2015
DOI: 10.1155/2015/836301
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Affects Erythropoiesis and Heart Mitochondrial Function in Mice

Abstract: Quercetin, a dietary flavonoid used as a food supplement, showed powerful antioxidant effects in different cellular models. However, recent in vitro and in vivo studies in mammals have suggested a prooxidant effect of quercetin and described an interaction with mitochondria causing an increase in O2 ∙− production, a decrease in ATP levels, and impairment of respiratory chain in liver tissue. Therefore, because of its dual actions, we studied the effect of quercetin in vivo to analyze heart mitochondrial functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…We previously reported that quercetin treatment also affected erythropoiesis. Immature erythroid populations showed a significant increase in the number of cells, while the iron-dependent cell populations of erythropoiesis for heme and hemoglobin biosynthesis significantly decreased in quercetin-treated mice [25].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We previously reported that quercetin treatment also affected erythropoiesis. Immature erythroid populations showed a significant increase in the number of cells, while the iron-dependent cell populations of erythropoiesis for heme and hemoglobin biosynthesis significantly decreased in quercetin-treated mice [25].…”
Section: Discussionmentioning
confidence: 93%
“…Male C57BL/6 mice were housed in groups of nine mice per cage and maintained at 22 • C on a 12:12-h light-dark cycle, with food and water ad libitum before the procedures. Moreover, male C57BL/6 mice (12 months of age) were daily injected intraperitoneally (i.p) with either 50 mg/kg quercetin (Sigma-Aldrich, Cat # Q4951, Merck KGaA, Darmstadt, Germany) (n = 9), or vehicle (5% DMSO) plus PBS (n = 9) for 15 days, according to the protocol previously described [25].…”
Section: Animalsmentioning
confidence: 99%
“…Food intake during quercetin treatment was not significantly reduced in mice on high-fat diets [26] or overweight humans [27]. However, mice receiving injections of quercetin (50 mg/kg) over 15 weeks showed significant body weight loss [28]. Henagan et al [29] reporting on B6 mice on a high-fat diet fed a high dose of quercetin (600 µg/day) observed greater fat gains compared to the controls, whereas a low dose (50 µg/day) significantly reduced fat.…”
Section: Discussionmentioning
confidence: 94%
“…Mfn2 (Ruiz et al, 2015). In isolated rat liver mitochondria, quercetin interacted with the mitochondrial membrane and significantly inhibited respiration (Dorta et al, 2008(Dorta et al, , 2005.…”
Section: Discussionmentioning
confidence: 97%